Autoimmune pituitary inflammation - Krzewski, Szymon; Baranowski, Mateusz; Wzorek, Katarzyna (Journal of Education, Health and Sport, 2022)
Autoimmune Hypophysitis (AH) is often refereed in the literature as lymphocytic pituitary inflammation. It is the most common form of rare, chronic inflammation states affecting this gland. In most cases it has autoimmune character. Symptoms of pituitary inflammation are mostly headaches, dysfunction of anterior and/or posterior pituitary lobe and visual disturbances. Diagnostics is extremely difficult and inflammation itself is probably diagnosed too rare. Autoimmune Hypophysitis coexist with other autoimmune endocrinopathies. The golden standard in Autoimmune Hypophysitis diagnosis is biopsy and magnetic resonance imaging (MRI) is also used. In relation to rare occurrence of the Autoimmune Hypophysitis, varied clinical picture and lack of standardized research on large group of patients there are no described standards of conduct with those patients.